C17. Can we improve the clinical manifestation of superior vena cava syndrome without treat the underlying disease?. (23rd November 2021) - Mappangara, Idar; Syamsuddin, Deni; Idul, Hafiz
Abstract: Background: Superior vena cava syndrome (SVCS) is a clinical manifestations from obstruction of superior vena cava that has thin wall. The main goals of SVCS management are to relieve the symptom and give therapy for the underlying disease. For now, there some additional therapies that connected to this disease such as steroid, diuretic, and anticoagulant. Flavonoid which a derivate from gamma benzopyrone has pharmacodynamics mechanism that appropriate with SVCS. Case Summary: We reported a male 35 years old came with SVCS typical manifestations. Then, we done some additional examinations, and we establish the diagnose with SVCS et cause anterior mediastinum mass suspected thymoma. The patient was planned to done histology biopsy, but the patient was refused to done any examination or interventions. We already gave diuretic, Vit-K antagonist anticoagulant, and high dose in short period steroid, but there was no any clinical improvement. Then, we add flavonoid hesperidin-diosmin, and there was clinical improvement after 1 months. Discussion: Based on the management algorithm of SVCS, we should done histology biopsy to this patient to establish the main cause of SVCS, so we can treat the patient by the cause. In literatures about SVCS, there was no any pharmacotherapies that believed can give clinical improvement, including steroid, diuretics, and anticoagulant. Flavonoid that has pharmacodynamics such as anti-inflammation, improve venous tone, increase lymphatic drainage appropriate with the clinical pathomechanism of SVCS. So it may has rational therapeutic effect to this patient.